2016
DOI: 10.2174/1389203717666151201191658
|View full text |Cite
|
Sign up to set email alerts
|

Disorder in Milk Proteins: Formation, Structure, Function, Isolation and Applications of Casein Phosphopeptides

Abstract: This article is a continuation of a series of reviews on the presence and the role of intrinsic disorder in milk proteins in the journal of Current Protein and Peptide Science. The focus of this article is on casein phosphopeptides, which are liberated during digestion of the milk protein casein. Structurally these phosphopeptides have multiphosphorylated regions making them highly charged. The high degree of charge coupled with relatively low instances of hydrophobic amino acids makes them intrinsically disor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…In the 90th minute, high molecular peptide fractions are absent ( Figure 6). Similar results with a large number of various low molecular weight phosphopeptides are described in other scientific researchs [21,22]. Figure 6.…”
Section: Gel Filtration and Electrophoresis Of Proteolysis's Productssupporting
confidence: 88%
“…In the 90th minute, high molecular peptide fractions are absent ( Figure 6). Similar results with a large number of various low molecular weight phosphopeptides are described in other scientific researchs [21,22]. Figure 6.…”
Section: Gel Filtration and Electrophoresis Of Proteolysis's Productssupporting
confidence: 88%
“…Gaucheron et al 31 estimated that cations are bound to α-casein and β-casein in the following affinity order: Fe > Zn > Ca. Zinc was found with 3 CPP (casein phosphopeptide) and the fraction containing α-casein and the 3 CPPs containing amino acids (glutamic acid, serine and phosphoserine), showing the Zn-complexes formation 23,32 . Moreover, the Zn distribution between casein, whey and other components may be affected by pH, heat and other cations present in the diet.…”
Section: Samples / Kdamentioning
confidence: 97%
“…Naqvi et al 23 reported that it was also possible to observe that Ca, Fe, Mg and Zn were mainly associated with colloidal calcium phosphate in casein micelles. For soybeans, 80% of the extracted proteins are βconglycine (7S) and glycine (11S).…”
Section: Gel Electrophoresismentioning
confidence: 99%
“…This is why the NaCasstabilized emulsion can be formed and broken within 1 min. Furthermore, the phosphoserine clusters can dynamically bind to the positive ions to form a positively charged layer around the localized micelles, serving as a vehicle for capturing ions, [33][34][35] providing theoretical support for strong salt tolerance, and thus contributing to the indenitely reversible pH-responsive cyclability ( Fig. S7 †) that cannot be found in other common proteins.…”
Section: Andmentioning
confidence: 99%